Characteristic Levels of Total Petroleum Hydrocarbons in Soil, Sediment and Surface Water of an Oil Impacted Area in the Niger Delta - Iwegbue, C.M.A.; Nwajei a, G.E.; Arimoro, F.O. (Biological Sciences - PJSIR, 2007)
Soi l , bottom sed i m ents and su rface water were co ll ected at severa l po i nts i n A bal agada-A boh area i n th e N i ger del t a, N i geri a, t h at h ad prev i ousl y recei ved spi ll ed crude oi l. Th e sampl es were anal yzed for tot a l petroleum h ydrocarbo n conten ts. Petrol eum h ydroca rbon con cen trati ons vari ed sign i fican t l y amon g va riou s en vi ron m en ta l m at rices. Th e con cen trat ions ranged w i del y between 2.80-785.6 mg/ kg, 2.84-804.74 mg/k g, 0.30-865.64 mg/kg and O 03-22.99 mg/kg for su r face water, sed i m en t s, topso i l and subsoi l , respectivel y. The sampl es sh owed e l evated con centration s of h yd rocarbon w h en compared to t h e control si te.